PENGARUH DOSIS INOKULUM DAN WAKTU FERMENTASI OLEH RHIZOPUS ORYZAE TERHADAP PENINGKATAN NILAI GIZI BUNGKIL BIJI JATROPHA CURCAS L. - Tuti Kurniati (JURNAL ISTEK, 2011)
The Jatropha curcas oil extraction process potentially produce 1 (one) ton/ha of seed cake of 5 ton of Jatropha curcas fruit process into 2 ton/ha of Jatropha curcas oil. This solid organic waste has high potency as broiler feeding. However, the problem is the nutrition value of jatropha seed cake, because the seed cake contains too high raw fat and raw protein that can not be digested directly. Fermentation is one of the method to improve the nutrition value of seed cake. In this research, Rhizopus oryzae was used as fermentation agent of jathropa seed cake. This research is aimed to obtain the optimal inoculum dosage and fermentation duration to improve nutrition value of Jatropha curcas seed cake. The experiment used random factorial method with three times repetition. The factor for the first treatment is fermentation duration, 72 hours, 96 hours and 120 hours. The factor for the second treatment was inoculum dosage, that comprised three degree, 2 g/kg, 3 g/kg, and 4 g/kg. Measured parameter were proximate analysis of raw protein and fat content of fermentation product. The research’s result shows the change of nutrient content in Jatropha curcas seed cake after fermentation. The results showed that highest increase of raw protein (7,97%) was achieved by 3g/kg inoculum dosage and 120 hours fermentation duration. The highest decrease in raw fat (82,46,%) achieved by 4g/kg inoculum dosage and 96 hours fermentation duration. From its effectivity, it is obtained that the optimal inoculum dosage is 3 g/kg with optimal fermentation duration which is 120 hours that yield the best nutrient quality in Jatropha curcas seed cake fermentation.